Expression profiling of genes involved in the formation of aroma in two peach genotypes. (8th October 2012) - Pirona, R.; Vecchietti, A.; Lazzari, B.; Caprera, A.; Malinverni, R.; Consolandi, C.; Severgnini, M.; De Bellis, G.; Chietera, G.; Rossini, L.; Pozzi, C.
Abstract The expression profile of flavour‐related genes during ripening was investigated in two peach genotypes, Bolero and OroA, which have been selected for their contrasting aroma/ripening behaviour. A new peach microarray containing 4776 oligonucleotide probes corresponding to a set of ESTs specifically enriched in secondary metabolism (μPEACH2.0) was designed to investigate transcriptome changes during three fruit ripening stages, revealing 1807 transcripts differentially expressed within and between the two genotypes. Differences in the expression of genes involved in the biosynthesis of aroma compounds were detected during the ripening process within and between the two genotypes. In particular, a subset of 12 transcripts involved in metabolism of esters, norisoprenoids, phenylpropanoids and lactones, varied in expression during ripening and between Bolero and OroA.